Christian - Zen Dialogue : Sacred Stories as a Starting Point for Interfaith Dialogue - Joseph, Jijimon Alakkalam (Book collections on Project MUSE., 2021)
"This book is an attempt to contribute to interfaith-dialogue initiatives spearheaded by the Catholic Church with Zen, one of the major and fast-growing spiritual traditions in East Asia. ... Christian - Zen Dialogue focuses on narratives of faith in Christianity and Zen. Can these sacred stories--gospel stories of Jesus and Chan/Zen stories (Kōans)--be a starting point for dialogue between the two faiths? The book focuses on two aspects: First, what model of interfaith dialogue can help Catholics and Zen followers of all walks of life engage in faith dialogue while remaining in their own life situations? Second, how can they make use of the common elements found in their narratives of faith as the most appropriate starting point for dialogue between them? To achieve the intended results, Joseph applies the hermeneutic phenomenological approach of Paul Ricoeur."--Publisher.